Orbital Period Change Analysis of a Contact Binaries System V416 Gem - Chaiwarakorn, Sommkorn; Maithong, Wiraporn (YRU Journal of Science and Technology, 2021)
The V416 Gemini binary star system (V416 Gem) is a W UMa eclipsing contact binary system with an eclipsing period of about 0.25614 day. Light curves of V416 Gem was constructed in Visual and Red wavelength bands from CCD Photometric System Data observation by using 0.7-meter Reflecting Telescope at the Regional Observatory for the Public, Chachoengsao, Thailand on 18 December 2018, UT. The period change rate analysis of this binary star system was calculated to present time of minimum light and the O-C curve of V416 Gem which is constructed from the database table of Bob Nelson, fitted by Quadratic Polynomial Fitting Method. The results showed that the orbital period of V416 Gem had been increased continuously at a rate of -1.21 × 10-5 day/year. That was corresponded of angular momentum loss theory.